Channels of Poverty Reduction in South Africa - Mateko, Freeman Munisi; Habiyaremye, Alexis (Acta Universitatis Danubius. Œconomica, 2025)
Poverty reduction is essential for economic development and is a key sustainable development goal that all nations must achieve by 2030. Objectives: The objectives of the study were to identify the mechanisms of poverty reduction in South Africa and analyze poverty trends. Approach: Data were gathered from the World Bank portal. Cointegration analysis, Error Correction Model and autoregressive distributed lag techniques were used to estimate the relationships between variables. Results: Our findings indicate that limited access to productive resources (due to past dispossession and segregation policies), ineffective governance, were significant drivers of poverty. The channels of poverty reduction go through stronger industrialisation and a stimulus to increase remittances and FDI and drive up the economic growth rate. Implications: Policy recommendations emphasized the need for South Africa to attract foreign direct investment, promote sustainable economic growth, and enhance industrialization efforts to effectively tackle poverty and improve living standards across the country. Value: The research offers evidence-based solutions to poverty reduction in South Africa.